PERLINDUNGAN HUKUM TERHADAP KEPENTINGAN PARA KREDITOR AKIBAT ACTIO PAULIANA DALAM HUKUM KEPAILITAN - Winda Swari, Ida Ayu Kade; Dirksen, A. A. Ngurah Gede; Wiratni Darmadi, A. A. Sagung (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014)
In bankruptcy proceedings, not uncommon deeds committed by the debtor to hide their wealth to avoid the settlement of property made by the Curator. Debtor is bad faith, will divert wealth to others in various ways. Actio pauliana an effort given by Law Number 37 of 2004 on Bankruptcy and Suspension of Payment to protect the interests of creditors of the fraudulent acts committed by the debtor. By using normative research it is known the position of the creditors in the bankruptcy law and the legal protection of the interests of the creditors as a result of actio pauliana.
Keywords: Bankrupty, Legal Protection, Creditor, Actio Pauliana